Controlling Costs and Margins of Engineered Systems. Issue 1 (29th May 2019) - Zhu, Haifeng
ABSTRACT: Designing systems with adaptability in mind is useful in dealing with today's dynamic changes in technologies, markets, and user demands. This article summarizes recent work on adaptability studies for engineered systems. We first present the adaptability concept for engineered systems, and the evaluation of missions/requirements needed for this concept. We then review the improved design process and design methods for systems to achieve high adaptabilities. Finally, we show the potential impact of adaptability to procurement methods and risk management. We use a heating, ventilation, and air conditioning (HVAC) example to illustrate these processes and methods that help maximize mission performance, reduce cost, and increase competitive advantages for a manufacturing product.